Effects of post-fermentation on the flavor compounds formation in red sour soup - Zhou, Xiaojie; Zhou, Wenhua; He, Xiaojie; Deng, Yaxin; Li, Liangyi; Li, Ming; Feng, Xuzhong; Zhang, Lin; Zhao, Liangzhong (Frontiers in Nutrition, 2022)
Red Sour Soup (RSS) is a traditional fermented food in China. After two rounds of fermentation, sour soup has a mellow flavor. However, the microbial composition and flavor formation processes in post-fermentation in RSS are unclear. This study investigates the bacteria composition of RSS during the post-fermentation stage (0–180 days) using high-throughput sequencing. The results show that lactic acid bacteria (LAB) are dominant during the post-fermentation process, and their abundance gradually increases with fermentation time. Additionally, gas chromatography-mass spectrometry was used to detect volatile flavor compounds in the post-fermentation process. Seventy-seven volatile flavor compounds were identified, including 24 esters, 14 terpenes, 9 aromatic hydrocarbons, 9 alkanes, 6 heterocyclic compounds, 3 alcohols, 3 acids, 3 ketones, 2 phenols, 2 aldehydes, 1 amine, and 1 other. Esters and aromatic hydrocarbons are the main volatile compounds in RSS during the post-fermentation process. Orthogonal partial least squares screening and correlation analysis derived several significant correlations, including 48 pairs of positive correlations and 19 pairs of negative correlations. Among them, Acetobacter spp., Clostridium spp. and Sporolactobacillus spp. have 15, 14, 20 significant correlation pairs, respectively, and are considered the most important bacterial genera post-fermentation. Volatile substances become abundant with increasing fermentation time. LAB are excessive after more than 120 days but cause a drastic reduction in volatile ester levels. Thus, the post-fermentation time should be restricted to 120 days, which retains the highest concentrations of volatile esters in RSS. Overall, these findings provide a theoretical basis to determine an optimal post-fermentation time duration, and identify essential bacteria for manufacturing high-quality starter material to shorten the RSS post-fermentation processing time.